Association of Vitamin D with the TaqI Polymorphism of the VDR Gene in Older Women Attending the Basic Health Unit of the Federal District, DF (Brazil). (24th September 2020) - de Souza Freitas, Renata; Fratelli, Caroline Ferreira; de Souza Silva, Calliandra Maria; Lima, Luciano Ramos de; Stival, Marina Morato; da Silva, Izabel Cristina Rodrigues; Schwerz Funghetto, Silvana
Abstract : Aging is accompanied by various functional modifications determined by their environment, lifestyle, nutrition, and genetics. Based on these factors, it is essential to verify the vitamin deficiency in the elderly population. Hypovitaminosis D is commonly present in human aging, increasing the chances of developing noncommunicable chronic diseases. The VDR gene TaqI polymorphism may modify the vitamin D metabolic pathway by altering the interaction between the vitamin D receptor and the active circulating vitamin D. Therefore, this study aimed to investigate the association between serum vitamin D and biochemical and genetic factors, considering the TaqI polymorphism of the VDR gene, in an elderly population of the Federal District. The study was a descriptive, case-control, quantitative, and cross-sectional type and was conducted in two basic health units in the administrative region of Ceilândia, Federal District, DF, Brazil, with women aged 60 years or older. Anthropometric, biochemical, and genetic parameters (VDR TaqI polymorphism) were evaluated. The adopted significance level was 5%, and statistical analyses were performed using the SPSS version 20.0 program. The study consisted of 128 participants. The most prevalent age was from 60 to 65 years ( N = 53; 41.4%). 66 elderly (51.6%) were part of the case group (hypovitaminosis D), while 62 were in the control group. In the case group, 30.2% had grade I obesity, 77.3% were hypertensive, and 51.5% were diabetic. The TT genotype was present in 47% of the case group and 54.8% in the control group (p = 0.667 ). There was no association between serum vitamin D levels and the VDR gene variant TaqI polymorphism in an elderly Brazilian population.